Bioremediation for Environmental Sustainability (IntechOpen, 2025)
This book highlights bioremediation’s role in detoxifying polluted environments using plants, microbes, and fungi. It offers innovative, eco-friendly soil and water remediation strategies, integrating phytoremediation, microbial techniques, and technological advancements to enhance environmental restoration. This book includes six chapters. The first chapter, Phytoremediation: The Green Solution, explores plant-based pollutant absorption and details mechanisms and applications for soil and water cleanup. The second chapter, Application of Fruit Wastes in the Bioremediation of Heavy Metals: Mechanism, Challenges and Prospects, examines organic fruit components as cost-effective agents for binding and removing toxic metals. The third chapter, Geochemical Processes Controlling Metals (Pb, Zn) Mobility during Amended Phytostabilization on Sulfidic Mine Tailings, examines the geochemical processes in the rhizosphere of sulfidic mine tailings during phytostabilization, revealing that plant activity lowers pH and increases metal release, while amendment additions neutralize acidity through three geochemical processes. The fourth chapter, Innovations in Herbicide Bioremediation: Green Solutions for Soil Contamination, presents biotech strategies that combine phytoremediation, microbial degradation, and mechanized tools to restore herbicide-contaminated soil. The fifth chapter, Mycoremediation: An Innovative and Sustainable Approach, discusses fungi’s ability to break down hydrocarbons, heavy metals, and toxins, emphasizing species-specific efficiency and real-world ecosystem restoration. The sixth and final chapter, The Role of Bioremediation in Achieving Environmental Sustainability, provides a comprehensive discussion on the impact of bioremediation in advancing sustainability and its contribution to multiple sustainable development goals. Each chapter is explored in detail, demonstrating bioremediation’s vital role in addressing environmental challenges through responsible and effective solutions. Gratitude is extended to contributors, editors, and publishers for their collaborative efforts in producing this resource for researchers, practitioners, and policymakers.